Astrocytes as an HIV Reservoir: Mechanism of HIV Infection - Li, Guan-Han; Henderson, Lisa; Nath, Avindra (Current HIV Research, 2016)
If we have any hope of achieving a cure for HIV infection, close attention to the cell types capable of getting infected with HIV is necessary. Of these cell types, astrocytes are the most ideal cell type for the formation of such a reservoir. These are long-lived cells with a very low turnover rate and are found in the brain and the gastrointestinal tract. Although astrocytes are evidently resistant to infection of cell-free HIV in vitro, these cells are efficiently infected via cell-tocell contact by which immature HIV virions bud off lymphocytes and have the ability to directly bind to CXCR4, triggering the process of fusion in the absence of CD4. In this review, we closely examine the evidence for HIV infection of astrocytes in the brain and the mechanisms for viral entry and regulation in this cell type, and discuss an approach for controlling this viral reservoir.
Keywords: endocytosis